(untitled) (Journal of actual problems of jurisprudence, 2018)
The research topic is devoted to the analysis of license agreements in English contract law. The purpose of this article is to define the concepts and legal nature of license agreements in English law and to establish opportunities for improving Kazakhstan’s legislation. For these purposes, the author analyzed the concepts of «license agreements» in the Anglo-Saxon legal system, considered the legal basis for licensing IP rights in the UK. This article also provides an overview of the types of licenses, the form and content of license agreements, the types of royalties, as well as some factors that affect the licensing fees under UK law. The main results of the study allow us to determine the license agreement in English law as «an agreement between the intellectual property owner (licensor) and the other party (the licensee) on granting permission to use the object of intellectual activity in a certain way.» Such provisions as quality control of the licensed product and confidentiality of the contract are also considered in this article. In this regard, the study has a theoretical value, since it allows to identify possible issues of perception and application of English law rules in national law, in intellectual property law. Key words: licensing of intellectual property rights, license agreement, intellectual property, English contract law, UK legislation on intellectual property, exclusive license, patents, trademarks.